Nutrisi Seimbang untuk Unggas: Memahami Pentingnya Protein dan Serat: Balanced Nutrition for Poultry: Understanding the Importance of Protein and Fiber - Putri, Shefani Eka; Majid Abdullah, Fathul; Septiyaningsih, Reni; Aulia, Fara; Puji Rahayu, Tri (Fakultas Peternakan Universitas Jambi, 2025)
Background: Feed is crucial for the growth and productivity of livestock. When designing feed, the main components to consider include protein, fiber, carbohydrates, fat, minerals and vitamins. Furthermore, ensuring sufficient nutrition is essential. Protein and crude fiber can determine the quality of poultry feed. Protein generally has a real influence on growth, tissue repair, feather development, metabolic function, formation of enzymes and hormones, body maintenance, and as a basic component in egg formation. The crude fiber content in feed has a significant effect on livestock performance and growth because it stimulates digestive tract movement. Reviews: This article will briefly review the nutritional needs of poultry from the need for protein, fiber, carbohydrates, fat, minerals and vitamins